Visualizing water-filled versus embolized status of xylem conduits by desktop x-ray microtomography - Suuronen, Jussi-Petteri (BioMed Central, 2013)
BACKGROUND: The hydraulic conductivity of the stem is a major factor limiting the capability of trees to transport water from the soil to transpiring leaves. During drought conditions, the conducting capacity of xylem can be reduced by some conduits being filled with gas, i.e. embolized. In order to understand the dynamics of embolism formation and repair, considerable attention has been given to developing reliable and accurate methods for quantifying the phenomenon. In the past decade, non-destructive imaging of embolism formation in living plants has become possible. Magnetic resonance imaging has been used to visualize the distribution of water within the stem, but in most cases it is not possible to resolve individual cells. Recently, high-resolution synchrotron x-ray microtomography has been introduced as a tool to visualize the water contents of individual cells in vivo, providing unprecedented insight into the dynamics of embolism repair. We have investigated the potential of an x-ray tube -based microtomography setup to visualize and quantify xylem embolism and embolism repair in water-stressed young saplings and shoot tips of Silver and Curly birch (Betula pendula and B. pendula var. carelica). RESULTS: From the microtomography images, the water-filled versus gas-filled status of individual xylem conduits can be seen, and the proportion of stem cross-section that consists of embolized tissue can be calculated. Measuring the number of embolized vessels in the imaged area is a simple counting experiment. In the samples investigated, wood fibers were cavitated in a large proportion of the xylem cross-section shortly after watering of the plant was stopped, but the number of embolized vessels remained low several days into a drought period. Under conditions of low evaporative demand, also refilling of previously embolized conduits was observed. CONCLUSIONS: Desktop x-ray microtomography is shown to be an effective method for evaluating the water-filled versus embolized status of the stem xylem in a small living sapling. Due to its non-destructive nature, the risk of inducing embolisms during sampling is greatly reduced. Compared with synchrotron imaging beamlines, desktop microtomography offers easier accessibility, while maintaining sufficient resolution to visualize the water contents of individual cells.